Eksplorasi Potensi Kuliner Lokal Berkelanjutan dengan Pendekatan Eco-Packaging - Utami, Ni Luh Putu Sri; Suarsana , I Wayan; Darsana , I Made; Arnawa, I Nyoman; Suartana , I Wayan; Darojat, Alfian Noor; Iqbal, Muhammad; Aryana , I Wayan Putu Sucana; Suwandana , I Made Adi; Rahayu , Luh Riniti (Penerbit Goodwood, 2025)
Purpose: This study aims to explore the potential of local culinary products in Penatih Dangin Puri Village, Denpasar, and to develop strategies for implementing environmentally friendly packaging (eco-packaging) as a means to strengthen sustainable village-based economic development. Methodology/approach: The study was conducted in Penatih Dangin Puri Village, Denpasar, through a community service program involving local micro, small, and medium enterprises (MSMEs) in the culinary sector. A participatory qualitative approach was applied, including focus group discussions, direct observation, and thematic analysis. Activities consisted of socialization sessions, culinary innovation training using local ingredients, introduction to eco-packaging technologies, branding and digital marketing workshops, and product showcase events. Results/findings: The program identified high-potential culinary products based on red rice, coconut, and traditional spices with strong cultural and economic value. The application of eco-packaging improved product aesthetics, market competitiveness, and environmental awareness among business owners. Collaborative networks between MSMEs, village authorities, and creative communities were established, creating a foundation for sustainable economic ecosystems. Conclusions: The study shows eco-packaging and local culinary integration enhance sustainability, community empowerment, and green entrepreneurship in rural development. Limitations: The study’s short duration limited evaluation of long-term impacts, including sustained eco-packaging adoption and continuous market performance measurement. Contribution: This study offers a replicable model for integrating local culinary heritage with eco-friendly entrepreneurship to support sustainable rural development.